Two-Way Selection for Daily Gain and Feed Conversion in a Composite Rabbit Population - Moura, Ana Silvia Alves Meira Tavares [UNESP]; Kaps, M.; Vogt, D. W.; Lamberson, W. R. (My University, 1997)
We conducted a two-way selection experiment in a composite rabbit population to investigate the responses to selection for postweaning ADG and feed conversion (FC). Two generations of crossing, followed by four generations of random pair matings, preceded three generations of selection. Selection was practiced within four lines: high-feed conversion (HFC), low-feed conversion (LFC), high gain (HG), and low gain (LG). Data on 1,446 rabbits from the random mating and selection generations were fitted to an animal model to estimate heritabilities of and the genetic correlation between ADG and FC. The two-trait model included rabbit and common litter random effects and line, generation, and sex fixed effects. Estimates of heritability of ADG and FC were .48 and .29, respectively, and the genetic correlation between them was -.82. Common litter environmental effects accounted for a proportion of .11 and . 13 of the phenotypic variation of the two traits, respectively. For ADG (in g/d) the regressions of mean breeding values on generation number during the selection period were 1.23 ± .12 (P < .01) in the HG line and -.86 ± .12 (P < .01) in the LG line; the regressions for FC (in g feed/g gain) were -.07 ± .01 (P < .01) in the HFC line and .03 ± .01 (P < .05) in the LFC line. Selection for ADG was effective in improving ADG and FC.
Keywords: Feed Conversion; Genetic Parameters; Growth; Rabbits; Selection; animal; biological model; eating; energy metabolism; environment; female; genetic selection; genetics; growth, development and aging; male; phenotype; physiology; rabbit; regression analysis; weight gain; Animals; Eating; Energy Metabolism; Environment; Female; Male; Models, Biological; Models, Genetic; Phenotype; Regression Analysis; Selection (Genetics); Weight Gain